2018
DOI: 10.3390/w11010035
|View full text |Cite
|
Sign up to set email alerts
|

Water Footprint and Crop Water Usage of Oil Palm (Eleasis guineensis) in Central Kalimantan: Environmental Sustainability Indicators for Different Crop Age and Soil Conditions

Abstract: Various issues related to oil palm production, such as biodiversity, drought, water scarcity, and water and soil resource exploitation, have become major challenges for environmental sustainability. The water footprint method indicates that the quantity of water used by plants to produce one biomass product could become a parameter to assess the environmental sustainability for a plantation. The objective of this study is to calculate the water footprint of oil palm on a temporal scale based on root water upta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
0
23
2
3
Order By: Relevance
“…Differences between our results and some of those reported by the literature may be associated to different soil types, depth of the root systems and soil hydraulic properties (Campos et al, 2017;Safitri et al, 2019). In addition to that, some errors may occur in K cbrfbased water balance due to the difficulty in obtaining cloud-free images in regions where oil palm is cultivated (Ng et al, 2012), as exhibited in Fig.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Differences between our results and some of those reported by the literature may be associated to different soil types, depth of the root systems and soil hydraulic properties (Campos et al, 2017;Safitri et al, 2019). In addition to that, some errors may occur in K cbrfbased water balance due to the difficulty in obtaining cloud-free images in regions where oil palm is cultivated (Ng et al, 2012), as exhibited in Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…Nelson et al (2006) carried out a study with oil palm in Papua New Guinea and reported an ET a value of 4.1 mm d -1 in an 8-year oil palm plantation. Safitri et al (2019) registered average daily ET a rates of 3.07 mm d -1 (K c =0.68) and 3.51 mm d -1 (K c =0.7) by a seven and 8-year-old oil palm stand in spodosol, respectively. Antonini et al (2015) reported ET a between 4.1 and 5.7 mm d -1 (K c =1.1) in irrigated 7-year-old oil palm trees under the Brazilian Tropical Savanna during the driest period of the year.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations